2020
DOI: 10.1111/jace.17526
|View full text |Cite
|
Sign up to set email alerts
|

Role of grain constraint on the martensitic transformation in ceria‐doped zirconia

Abstract: Zirconia polycrystals have historically suffered from catastrophic cracking during the tetragonal-monoclinic martensitic transformation. Recently, transformation-induced cracking has been avoided by doping to achieve crystallographic compatibility between the transforming phases. However, these materials showed depressed transformation temperatures and incomplete transformation, the causes for which are yet unknown. In this work, we probe these phenomena by performing a comparative study of sintered pellets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
(154 reference statements)
1
3
0
Order By: Relevance
“…The main aim of this work was to analyze this peculiar phase development pattern of BaCO 3 in connection to the same being given a shape (via compaction and heat-treatment) or kept free as loose powders. A similar difference on other materials has been recently investigated by our group , and others. , Prof. Schuh’s group conducted research on different ZrO 2 –CeO 2 systems in the form of pellet and oligocrystalline powders. The findings indicated that the sintered zirconia ceramic had a strongly suppressed phase transformation temperature.…”
Section: Introductionsupporting
confidence: 76%
“…The main aim of this work was to analyze this peculiar phase development pattern of BaCO 3 in connection to the same being given a shape (via compaction and heat-treatment) or kept free as loose powders. A similar difference on other materials has been recently investigated by our group , and others. , Prof. Schuh’s group conducted research on different ZrO 2 –CeO 2 systems in the form of pellet and oligocrystalline powders. The findings indicated that the sintered zirconia ceramic had a strongly suppressed phase transformation temperature.…”
Section: Introductionsupporting
confidence: 76%
“…This suggests that the shaped ceramic experienced a hindrance during sintering that eventually restricted the growth of grains. In our first report, we tried explaining this using a factor, labeled “consolidation factor.” Few months later, Prof. Schuh's research group at MIT, USA 10 observed similar effect (consolidation factor) for binary ZrO 2 –CeO 2 systems. The authors observed that the phase transformation temperature was strongly suppressed in sintered zirconia ceramics.…”
Section: Introductionmentioning
confidence: 76%
“…In the case of SMAs, previous work has investigated the tendency of Cu-based SMAs to fracture along grain boundaries due to strain incompatibilities there [16][17][18]. In SMCs, grain boundary strain incompatibility is less studied, although recent work has provided significant insights [9,[19][20][21]. Pang et al [19] investigated the two-dimensional compatibility of the martensiteaustenite interface via the application of the cofactor conditions as a possible factor controlling the cracking of bulk polycrystalline zirconia-based SMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that samples with excellent interface compatibility could avoid cracking during thermal cycles and bulk compatibility is not necessarily the dominant cause of transformation-induced fracture. The same authors [20] analyzed the differences in thermally-induced transformation behaviors between ZrO 2 -CeO 2 oligocrystalline powders and sintered pellets. The role of grain boundaries in the damage evolution of yttria-doped zirconia subject to thermal cyclic loading was also discussed in [9,21].…”
Section: Introductionmentioning
confidence: 99%